1986
DOI: 10.1002/clc.4960090608
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of high‐density lipoprotein (hdl)‐2 and hdl‐3 in myocardial infarction survivors and in control subjects

Abstract: Summary: The serum concentration of several lipids, including high-density lipoprotein-cholesterol (HDL-C) and the HDL subfractions, HDL-2-C and HDL-3-C, were measured in 44 male and 26 female survivors of myocardial infarction and compared with those of a control group matched for age, sex, and body weight. Serum concentrations of total cholesterol (TC) and low-density lipoprotein (LDL-C) were significantly increased in patients as compared to control individuals. The total HDL-C concentration was lower in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Table 4 shows the serum levels of total lipids, lipoprotein lipids and apolipoproteins. PKU patients had significantly lower HDLc, lower HDL2c and higher non-HDLc levels, altogether indicating an atherogenic pattern [24, 25]. The non-HDLc levels (r = 0.486, p = 0.026), but no other blood lipid levels were significantly associated with the BMI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows the serum levels of total lipids, lipoprotein lipids and apolipoproteins. PKU patients had significantly lower HDLc, lower HDL2c and higher non-HDLc levels, altogether indicating an atherogenic pattern [24, 25]. The non-HDLc levels (r = 0.486, p = 0.026), but no other blood lipid levels were significantly associated with the BMI.…”
Section: Resultsmentioning
confidence: 99%
“…It can be classified into subtypes differing in density [46]. HDL2c has been suggested a more adequate risk indicator for cardiovascular disease in the general population than HDLc and HDL3c [24], although other studies could not confirm an association of CVD with HDL subclasses [47]. HDL subtypes have not been studied previously in PKU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol and triglycerides in the plasma were measured by enzymatic methods. HDL cholesterol was determined according to the method of Brugger et al [13].…”
Section: Methodsmentioning
confidence: 99%
“…Early epidemiological studies describe HDL2 as more accurate risk indicator for CVD. Indeed, myocardial infarction survivors had significant decreases in HDL2 ( Brugger et al, 1986 ), and HDL2 was inversely correlated with coronary heart disease risk ( Johansson et al, 1991 ). A large study of 4594 healthy patients demonstrated that a decrease in HDL2 was associated with increased CVD risk ( Musunuru et al, 2009 ) and patients with acute coronary syndrome displayed decreased levels of HDL2 and increased levels of HDL3 ( Tian et al, 2014 ).…”
Section: Hdl2 and Hdl3 Subclassesmentioning
confidence: 99%